A Model for Becoming an Inclusive Adult Educator: Designing for Disability - Tulare W. Park; Kayla D. Mohney; Erica R. Moore; Carol Rogers-Shaw (Adult Education Research Conference, 2022)
This evidence-based model of inclusive teaching offers knowledge and practical applications for adult educators. It provides strategies for equitably addressing all student needs, particularly those with disabilities.
Keywords: inclusive teaching; disability; adult education; UDL; evidence-based practices